Canine Central Nervous System Neoplasm Phenotyping Using Tissue Microarray Technique. (May 2017) - Spitzbarth, I.; Heinrich, F.; Herder, V.; Recker, T.; Wohlsein, P.; Baumgärtner, W.
Tissue microarrays (TMAs) represent a useful technique for the simultaneous phenotyping of large sample numbers and are particularly suitable for histopathologic tumor research. In this study, TMAs were used to evaluate semiquantitatively the expression of multiple antigens in various canine central nervous system (CNS) neoplasms and to identify markers with potential discriminative diagnostic relevance. Ninety-seven canine CNS neoplasms, previously diagnosed on hematoxylin and eosin sections according to the World Health Organization classification, were investigated on TMAs, with each tumor consisting of 2 cylindrical samples from the center and the periphery of the neoplasm. Tumor cells were phenotyped using a panel of 28 monoclonal and polyclonal antibodies, and hierarchical clustering analysis was applied to group neoplasms according to similarities in their expression profiles. Hierarchical clustering generally grouped cases with similar histologic diagnoses; however, gliomas especially exhibited a considerable heterogeneity in their positivity scores. Multiple tumor groups, such as astrocytomas and oligodendrogliomas, significantly differed in the proportion of positive immunoreaction for certain markers such as p75 NTR, AQP4, GFAP, and S100 protein. The study highlights AQP4 and p75 NTR as novel markers, helping to discriminate between canine astrocytoma and oligodendroglioma. Furthermore, the results suggest that p75 NTR and proteolipid protein may represent useful markers, whose expression inversely correlates with malignant transformation in canine astrocytomas and oligodendrogliomas, respectively. Tissue microarray was demonstrated to be a useful and time-saving tool for the simultaneous immunohistochemical characterization of multiple canine CNS neoplasms. The present study provides a detailed overview of the expression patterns of different types of canine CNS neoplasms.